The Role of Stakeholders in Ecotourism Development in Jatiluwih Tourism Village Area, Bali - Martadina, Yuvie; Ardiansyah, Imam (E-Journal of Tourism; Volume 10 Number 2 (September 2023), 2023)
Jatiluwih is one of the tourist destinations in Bali. The development of the Jatiluwih ecotourism area certainly requires participation and synergy between stakeholders. This is useful for obtaining the objectives and results of good area management. In the development and management of the Jatiluwih, the stakeholders involved in it are considered not optimal. The purpose of this study is to find out how big the role and interests of stakeholders are in the development of ecotourism in Jatiluwih . Method of this research is qualitative and quantitative research methods.  Analytical method for stakeholder using power-interest matrix grid. The number of participants in this study were 45 participants. Based on the results of  research and field observations conducted by researchers, it was found that there were 15 stakeholders divided into four quadrants. The conclusion of this study is that there are 3 subject stakeholders are travel agents, tourists, and local communities. The 6 key player groups are the Ministry of Tourism and Creative Economy, Bali Tourism Office, Tabanan Regency Government, Jatiluwih Village Government, Jatiluwih tourist attraction Management, and Jatiluwih Subak. 3 context setter groups are accommodation , restaurants, and customary stakeholders, and 3 crowd groups are academics, Jatiluwih health center, and media. Suggestions for 15 stakeholders in Jatiluwih are that they should increase collaboration and cooperation to strengthen relations between one another so that they can develop the tourist area into a coordinated, beautiful and neat tourist area, while still prioritizing tourism sustainability. Keywords : Ecotourism, Stakeholders, Tourism Village, Jatiluwih, Rice Terrace.